Financial Inclusion and Inclusive Growth : What Does It Mean for Sri Lanka? - Arandara, Rathnija (World Bank, Washington, DC, 2020)
This paper uses data from the National Financial Inclusion Survey 2018 to understand the determinants of financial inclusion in Sri Lanka and their significance for inclusive growth. The findings highlight that gender, education, and formal employment are important determinants of financial inclusion in the country. The results indicate that being a male, having better education, and having formal employment increase a person's access to, and usage of, formal finance. The results also suggest that despite high levels and gender parity in education, Sri Lankan women seem to access more informal finance (and less formal finance) compared with men. There is a general lack of familiarity and low use of digital finance among women. Comparative analysis using the World Bank Group’s Global Financial Inclusion (Global Findex) Database 2017 indicates that although Sri Lanka leads its regional peers in access to finance, it lags its more aspirational East Asian counterparts in usage of savings and credit products as well as digital finance. The paper's findings complement recent policy initiatives such as the National Financial Inclusion Strategy for Sri Lanka. The findings also help in designing targeted actions to address the remaining gaps in financial inclusion in Sri Lanka.